ANALISIS PERILAKU KELUARGA BALITA DAN KONDISI LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN PNEUMONIA PADA BALITA DI INDONESIA: LITERATURE REVIEW TAHUN 2012-2021 - Husein Umarush Shiddiq; R Azizah; Juliana Binti Jalaludin; Lilis Sulistyorini; Novi Dian Arfiani (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
ABSTRACTPneumonia is an acute respiratory infection that adversely affects the lungs caused by viruses, bacteria or fungi, where pneumonia accounts for 15 percent of under-five deaths in the world and resulted in 808,694 children dying in 2017 (WHO, 2019). The purpose of this study was to analyze family behavior and the condition of the physical home environment with the incidence of pneumonia in children under five in Indonesia. The method in this study is a literature review. The data sources in this study came from Google Scholar, Science Direct, and Pubmed then sorted according to the inclusion and exclusion criteria and obtained 28 research articles.The results of the analysis of several studies show that smoking habits of family members (83.3%), use of mosquito coils (50%), house occupancy density (72.7%), and type of house floor (50%) are associated with the incidence of pneumonia in children under five. . It is hoped that the puskesmas can make efforts to control the risk of pneumonia in toddlers by conducting periodic counseling about the dangers of smoking to toddlers and how to overcome them, as well as relating to factors that affect the physical condition of the home environment, especially in the density of residential houses with a house building area that should be sufficient. for the occupants in it.Keywords: Pneumonia Incidence, Literature Review, Family behavior, Home Physical Environment Condition.ANALISIS PERILAKU KELUARGA BALITA DAN KONDISI LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN PNEUMONIA PADA BALITA DI INDONESIA: LITERATURE REVIEW  TAHUN 2012-2021